BIMBINGAN MANASIK DALAM MENINGKATKAN MUTU IBADAH HAJI DAN UMRAH PADA JAMA’AH KBIHU QUBBATUL MUTTAQIN SUKABUMI - Irhan Ari Muhamad; Kenny Pebriani Kusnadi Putri (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Quality Improvement is a picture or characteristic of human resources and other resources that relate to several aspects that can be worked on to achieve good and quality improvement results. Therefore, improving the quality of KBIHU must be a serious concern, not only fixated on physical facilities and infrastructure, but must pay attention to the istitha'ah rituals of Hajj to guarantee the mabrur of the pilgrimage, as well as the ability and mastery of the rituals of Hajj and Umrah. The requirement of istitha'ah should also include mastery of religious aspects and knowledge. In the process of hajj and umrah rituals, there needs to be a test of reading the Qur'an and other religious knowledge. This research is a qualitative research in collecting data from informants. The data source used for this research is Primary Data, where the research data is obtained directly and processed directly from the object. Data collection techniques through interviews, observation and documentation. the mechanism for implementing Hajj and Umrah ritual guidance for improving the quality of pilgrims carried out by KBIHU Qubbatul Muttaqin Sukabumi has been running quite well in accordance with the method and form of implementation of ritual guidance that has been established.